INVESTIGAÇÃO ELETROQUÍMICA DA DEGRADAÇÃO DA CURCUMINA LIVRE E NANOENCAPSULADA - Barbosa, Marcelo Rodrigues (2016)
Curcumin is obtained from Curcuma long dry roots (Saffron), is a gold-colored material used around the world as a seasoning. Since ancient times, curcumin has been widely used in treating various. Curcumin is responsible both for its coloring characteristics as well as their biological activities. Because it has antioxidant properties and application in the treatment of various diseases curcumin has attracted the interest of many researchers. Several strategies are being studied to improve the bioavailability of curcumin in the body, one is the encapsulation of curcumin on nanoparticles, which allows a better pharmacological application. A polymer that has long been used for this nanoencapsulation is milk polyacid (PLA) which is a biocompatible and biodegradable material suitable for clinical applications. Electrochemical and is a quick and effective way in investigating these aspects allows also assess whether the charge transfer processes and their antioxidant activity undergo changes with the package. The antioxidant activity of a compound is often evaluated by cyclic voltammetry technique based on oxidation peak potential. This work aims to study the degradation of nanocoated curcumin PLA and the free curcumin at different pHs using electrochemical methods. All electrochemical studies were performed in a thermostatically controlled electrochemical cell of a single compartment with a maximum volume of 8 mL capacity. Studies achieved in this work regarding the degradation of curcumin showed that when the curcumin is nanocoated it is significantly more stable than the free curcumin, and it was observed that the activity of curcumin directly depends on the pH.